Accuracy of an extubation readiness test in predicting successful extubation in children with acute respiratory failure from lower respiratory tract disease - Faustino, Edward Vincent S. (Crit Care Med, 2017)
OBJECTIVE: Identifying children ready for extubation is desirable to minimize morbidity and mortality associated with prolonged mechanical ventilation and extubation failure. We determined the accuracy of an extubation readiness test (RESTORE ERT) in predicting successful extubation in children with acute respiratory failure from lower respiratory tract disease. DESIGN: Secondary analysis of data from the RESTORE clinical trial, a pediatric multicenter cluster randomized trial of sedation. SETTING: 17 pediatric intensive care units in the intervention arm. PATIENTS: Children 2 weeks to 17 years receiving invasive mechanical ventilation for lower respiratory tract disease. INTERVENTION: ERT in which spontaneously breathing children with oxygenation index ≤6 were placed on FiO(2) of 0.50, positive end expiratory pressure of 5 cm H(2)O, and pressure support. MEASUREMENTS AND MAIN RESULTS: Of 1,042 children, 444 (43%) passed their first ERT. Of these, 295 (66%) were extubated within 10 hours of starting the ERT, including 272 who were successfully extubated, for a positive predictive value of 92%. Among 861 children who were extubated for the first time within 10 hours of performing an ERT, 788 passed their ERT and 736 were successfully extubated for a positive predictive value of 93%. The median time of day for extubation with an ERT was 12:15H compared with 14:54H for extubation without an ERT within 10 hours (p<0.001). CONCLUSIONS: In children with acute respiratory failure from lower respiratory tract disease, an ERT, as described, should be considered at least daily if the oxygenation index is ≤6. If the child passes the ERT, there is a high likelihood of successful extubation.